Filling the biostratigraphical gap: First choristoderan from the Lower – mid-Cretaceous interval of Europe. (April 2019) - Reiss, Stefan; Scheer, Udo; Sachs, Sven; Kear, Benjamin P.
Abstract: Choristodera is a clade of extinct aquatic reptiles whose fossils have been found in freshwater and marginal marine deposits from Europe, Asia and North America. The European record is the most extensive, spanning at least the Middle Jurassic to early Miocene, and incorporates the stratigraphically oldest and youngest members of the group. Despite this, there is an unexplained ∼70 myr gap in European choristoderan fossil occurrences. Here we fill this hiatus with the discovery of an isolated choristoderan dorsal vertebra from the lower Cenomanian 'Rotkalk' red limestone facies of the Essen Greensand Formation in Mülheim/Ruhr, North Rhine-Westphalia, western Germany. This specimen represents the first identifiable European choristoderan from the Kimmeridgian–Campanian interval, and displays a diagnostic state combination including an amphiplatyan centrum with synapophyses on the transverse processes that are level with the neurocentral suture. The palaeobiogeographical distribution of choristoderans thus likely transected the entire Laurasian landmass throughout the Cretaceous, with perceived stratigraphical interstices being a result of incomplete sampling.